Developing and refining a programme theory for understanding how twenty mile per hour speed limits impact health. (September 2018) - Turner, Kieran; Jepson, Ruth; MacDonald, Bradley; Kelly, Paul; Biggs, Hannah; Baker, Graham
Abstract: Background and aim: Traffic speed is an important determinant of health, affecting both the frequency and severity of road traffic collisions and casualties. Reduced traffic speed may also improve conditions for walking and cycling. Twenty mile per hour (30km per hour) speed restriction schemes are one policy option for reducing traffic speeds. The aim of this study was to develop and refine a programme theory for understanding how such schemes may impact on health outcomes. Methods: The programme theory was developed through an iterative process. Firstly, a logic model (diagrammatic version of the programme theory) was created through discussions with 20 mph programme delivery staff from the local authority and through reviewing literature. The second stage consisted of interviews with key stakeholders, and focus groups with the public to further develop and refine the logic model. Data were analysed using Framework Method. Results: This study first presents an early stage logic model (phase 1) of how the 20 mph speed limit is proposed to work. Qualitative data are then presented (phase 2), describing potential mechanisms as to how the scheme could influence health outcomes through changing i) driver behaviour; ii) casualties and casualty severity; iii) walking and cycling behaviour; iv) air quality; and v) street pleasantness. Participants identified a need for driver education and enforcement in order to reduce speeds, and the importance of improving perceptions of safety for achieving increased walking and cycling. A refined version of the logic model is presented. Implications: The programme theory will be used as a framework to evaluate the implementation of 20 mph speed limit schemes in Edinburgh and Belfast, aiding in study design decisions such as outcome data to be collected and in the generation of specific testable hypotheses. Highlights: Programme theory developed to help understand health impacts of 20 mph speed limits. Education deemed necessary to achieve broad driver compliance with 20 mph limit. Speed differential and perceived safety identified paths to altering active travel. Modal shift away from cars identified as potential outcome, impacting air quality. Theory-based evaluations will determine effectiveness of schemes for policy makers.